Heat loss prevention in the delivery room in term and preterm infants - De Carolis, Maria Pia; Rubortone, Serena Antonia; Bersani, Iliana; Lacerenza, Serafina; Cota, Francesco; Garufi, Cristina; Romagnoli, Costantino (The Turkish Journal of Pediatrics, 2013)
This study was conducted to determine whether or not simultaneous use of additional measures to prevent heat loss and efficient training of caregivers influenced the incidence of hypothermia at birth. Two cohorts of term/late-preterm and preterm infants were compared before (Group IA and IB) and after (Group IIA and IIB) the introduction of additional measures and a specific training of caregivers. In term/late-preterm neonates of Group IIA, admission temperature was higher (36.3°C vs 36°C; p